"What a nurse suffers": Care left undone in seventeenth‐century Madrid. (22nd July 2019) - Langtree, Tanya; Birks, Melanie; Biedermann, Narelle
Abstract: Care left undone, interchangeably referred to as missed care, unfinished nursing care and task incompletion, is pervasive in contemporary healthcare systems. Care left undone can result in adverse outcomes for the patient, nurse and organization. The rhetoric that surrounds care left undone infers it is a contemporary nursing phenomenon; however, a seventeenth‐century Spanish nursing treatise, Instruccion de Enfermeros (Instructions for Nurses), challenges this assumption. Instruccion de Enfermeros was an instructional guide that was written for members of the Congregation of Bernardino de Obregon who worked as nurses at the Madrid General Hospital. The treatise provides a historical commentary on the daily roles, responsibilities and working conditions of the Obregonian nurses. Its content and context suggest the Obregonian nursing resource was consistently time poor due to a confluence of internal and external stressors. Consequently, the Obregonians were under considerable role strain resulting in inferior patient care. This article explores the antecedents of care left undone through a historical lens using exemplars from the 1625 edition of Instruccion de Enfermeros . Factors contributing to care left undone in Obregonian nursing will then be examined to offer insights into the similarities between what a nurse suffered 400 years ago and what exists in contemporary nursing practice.